2014
DOI: 10.4103/0974-8490.138257
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of insulin resistance by Rk1+ Rg5complex under endoplasmic reticulum stress conditions

Abstract: Background:Diabetes mellitus is a metabolic syndrome exaggerated by stress conditions. Endoplasmic reticulum stress (ERS) impairs the insulin signaling pathway making the diabetic conditions worsen. Pharmacological agents are supplied externally to overcome this malfunction. Ginsenosides from Panax ginseng C.A Meyer possesses many pharmacological properties and are used for the treatment of diabetes.Objective:To investigate the effects of the Rk1 +Rg5 complex on the amelioration of insulin resistance in 3T3-L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Out of the 28 studies included, 21 studies were related to the effectiveness of G-Rk1 only and seven studies were reported on the combined effects of G-Rk1 and G-Rg5. The most common study design was in vitro study with 22 studies ( Ahn et al, 2016 ; Ju et al, 2012 ; Kang et al, 2007 ; Kang et al, 2006 ; Kim et al, 2012 ; Kim et al, 2009 ; Kim et al, 2008 ; Kim et al, 2013b ; Ko et al, 2009 ; Kwak & Pyo, 2016 ; Lee et al, 2009 ; Lee et al, 2010 ; Lee, 2014 ; Lim et al, 2009 ; Liu et al, 2007 ; Park et al, 2002 ; Ponnuraj et al, 2014 ; Quan et al, 2015 ; Ryu et al, 2016 ; Siddiqi et al, 2014 ; Toh et al, 2011 ; Xue et al, 2017 ), while in vivo study was less common with only two studies ( Jing et al, 2006 ; Kim et al, 2010 ). The remaining four articles were both in vitro and in vivo studies ( Bao et al, 2005 ; Hu et al, 2017 ; Maeng et al, 2013 ; Park et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the 28 studies included, 21 studies were related to the effectiveness of G-Rk1 only and seven studies were reported on the combined effects of G-Rk1 and G-Rg5. The most common study design was in vitro study with 22 studies ( Ahn et al, 2016 ; Ju et al, 2012 ; Kang et al, 2007 ; Kang et al, 2006 ; Kim et al, 2012 ; Kim et al, 2009 ; Kim et al, 2008 ; Kim et al, 2013b ; Ko et al, 2009 ; Kwak & Pyo, 2016 ; Lee et al, 2009 ; Lee et al, 2010 ; Lee, 2014 ; Lim et al, 2009 ; Liu et al, 2007 ; Park et al, 2002 ; Ponnuraj et al, 2014 ; Quan et al, 2015 ; Ryu et al, 2016 ; Siddiqi et al, 2014 ; Toh et al, 2011 ; Xue et al, 2017 ), while in vivo study was less common with only two studies ( Jing et al, 2006 ; Kim et al, 2010 ). The remaining four articles were both in vitro and in vivo studies ( Bao et al, 2005 ; Hu et al, 2017 ; Maeng et al, 2013 ; Park et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies were categorized as high quality ( Hu et al, 2017 ; Kang et al, 2006 ; Kim et al, 2009 ; Kim et al, 2008 ; Ko et al, 2009 ; Kwak & Pyo, 2016 ; Lee et al, 2009 ; Lee, 2014 ; Lim et al, 2009 ; Liu et al, 2007 ; Maeng et al, 2013 ; Park et al, 2002 ; Quan et al, 2015 ; Ryu et al, 2016 ; Toh et al, 2011 ; Xue et al, 2017 ). Twelve studies ( Ahn et al, 2016 ; Bao et al, 2005 ; Jing et al, 2006 ; Ju et al, 2012 ; Kang et al, 2007 ; Kim et al, 2012 ; Kim et al, 2010 ; Kim et al, 2013b ; Lee et al, 2010 ; Park et al, 2015 ; Ponnuraj et al, 2014 ; Siddiqi et al, 2014 ) were categorized as moderate quality. Seven of them ( Ahn et al, 2016 ; Bao et al, 2005 ; Jing et al, 2006 ; Kim et al, 2013b ; Park et al, 2015 ; Ponnuraj et al, 2014 ; Siddiqi et al, 2014 ) focused on the effectiveness of combined (G-Rk1, G-Rg5), thus, they were downgraded in indirectness item of GRADE factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations